MODERN APPROACHES TO THERAPY OF PATIENTS WITH STATUS EPILEPTICISM. (CAHIERS MAGELLANES-NS, 2024)
Significance of the problem: In 2019, William Kaelin, Gregg Semenza, and Peter Ratcliffe received the Nobel Prize for their discoveries related to hypotoxicity. HIF-1α (Hypoxia-dependent factor 1-alpha) plays an important role in the adaptation of cells and control of metabolic processes under hypotoxic conditions. An imbalance in the level of HIF-1α can lead to the development of epilepsy and an increase in the number of seizures. The purpose of the study: to study the role of HIF-1α and the effectiveness of the drug Zoresan (zonisamide) in status epilepticus. Materials and methods: 77 patients (20-81 years old) were studied. The level of HIF-1α was measured by biochemical studies, and the results were compared to a healthy control group. Results: HIF-1α level was higher in patients with status epilepticus (598.04±173.86) and decreased in epileptic patients (248.10±54.43) and healthy subjects (140.73±33.92). . Through Zoresan treatment, fibrinogen levels in patients were normalized, which helped to eliminate hypoxia. Conclusion: HIF-1α level and fibrinogen elevation are important as markers of cerebral hypoxia. Zoresan drug is effective for epileptic patients and helps to protect neurons. This drug shows potential to improve long-term treatment outcomes.